Morphology, mechanical characterization and in vivo neo-vascularization of chitosan particle aggregated scaffolds architectures - Malafaya, P. B. (2008)
The present study intended to evaluate the performance of chitosan-based scaffolds produced by a particle aggregation method aimed to be used in tissue engineering applications addressing key issues such as morphological characteristics, mechanical performance and in vivo behaviour. It is claimed that the particle aggregation methodology may present several advantages, such as combine simultaneously a high interconnectivity with high mechanical properties that are both critical for an in vivo successful application. In order to evaluate these properties, micro-Computed Tomography (micro-CT) and Dynamical Mechanical Analysis (DMA) were applied. The herein proposed scaffolds present an interesting morphology as assessed by micro-CT that generally seems to be adequate for the proposed applications. At a mechanical level, DMA has shown that chitosan scaffolds have an elastic behaviour under dynamic compression solicitation, being simultaneously mechanically stable in the wet state and exhibiting a storage modulus of 4.21 ! 1.04 MPa at 1 Hz frequency. Furthermore, chitosan scaffolds were evaluated in vivo using a rat muscle-pockets model for different implantation periods (1, 2 and 12 weeks). The histological and immunohistochemistry results have demonstrated that chitosan scaffolds can provide the required in vivo functionality. In addition, the scaffolds interconnectivity has been shown to be favourable to the connective tissues ingrowth into the scaffolds and to promote the neo-vascularization even in early stages of implantation. It is concluded that the proposed chitosan scaffolds produced by particle aggregation method are suitable alternatives, being simultaneously mechanical stable and in vivo biofunctional that might be used in load-bearing tissue engineering applications, including bone and cartilage regeneration.